2011
DOI: 10.1007/s10792-011-9497-x
|View full text |Cite
|
Sign up to set email alerts
|

Patient satisfaction and postoperative pain with different postoperative therapy regimens after standardized cataract surgery: a randomized intraindividual comparison

Abstract: The purpose of this study was to evaluate if administration of artificial tears of high or low-viscosity improve cataract patients' satisfaction and postoperative pain after cataract surgery. Thirty consecutive patients undergoing bilateral cataract surgery under topical anesthesia were enrolled prospectively. Administration of the following postoperative therapies was randomized: for all participants, one eye was treated with "instant vision" (IV) therapy alone (IV-alone), i.e., this eye remained uncovered. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 11 publications
0
8
0
1
Order By: Relevance
“…The prevalence of pain decreased to 0–11% during the first 24 hr after surgery (Sipos et al. ). Recently, the effect of a subconjunctival injection of corticosteroid‐antibiotic solution was compared with iodine eye drops (Ahmed et al.…”
Section: Review Of the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of pain decreased to 0–11% during the first 24 hr after surgery (Sipos et al. ). Recently, the effect of a subconjunctival injection of corticosteroid‐antibiotic solution was compared with iodine eye drops (Ahmed et al.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Sipos et al. () showed that artificial tear therapy reduced significantly early painful ocular irritation symptoms at 1 hr after surgery, but no longer at 6 or 24 hr after surgery.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Moreover, data available on the perception of pain during ASA procedure and its frequency are scarce. 27 Our study evaluated intra-operatory pain finding that half the patients notice pain during surgery. Another novelty in the outcome of this study is that 73% of these patients referred to the same pain in both eyes and only 19% reported more pain in the second eye.…”
Section: Discussionmentioning
confidence: 99%
“… 31 NRS and VRS, which are validated scales, showed a high concordance between them and are equally sensitive in assessing acute pain after surgery. 27 In a review, these three scales for the assessment of postoperative pain intensity in adults were evaluated. 30 This study concluded with a novel idea.…”
Section: Discussionmentioning
confidence: 99%
“…Por lo tanto, una evaluación completa del dolor postoperatorio después de la cirugía de ASA se debería de realizar, como mínimo, durante este periodo de tiempo.Del mismo modo, el dolor intra-operatorio también es un tema importante. Los datos disponibles sobre la percepción del dolor durante la cirugía de ASA son escasos 129. Este estudio aporta como resultado novedoso el que la mitad de los pacientes refieren dolor durante la cirugía, y de ellos, el 73% experimentó igual dolor en ambos ojos y solo el 19% sintió más dolor en el segundo ojo operado.…”
unclassified